Legal Protection of Importing Companies From Import Duty Exemption of Imported Goods Sold to Representatives of Foreign Countries (Study of Decision Number 1265/B/Pk/Pjk/2017) - Sudirgo, Tony; Wagiman, Wagiman (Universitas Ekasakti, 2023)
The Customs Law, in its substance, regulates matters of customs administration, which includes export and import arrangements, tariffs and customs value, exemption from import duties, procedures for payment of import duties, prohibitions and restrictions on export-import, and criminal provisions related to customs. Even though there have been precise arrangements regarding certain goods that are exempt from payable import duties, in reality, on the ground, there are still disputes regarding import duties between business actors as importers and the Directorate General of Customs and Excise as executors of customs affairs for imported goods. This study discusses how the implementation of import duty exemption procedures by the Directorate General of Customs and Excise (DJBC) applies to imported goods belonging to Representatives of Foreign Countries, in this case, the British Embassy in Indonesia, carried out by PT. Toyota Astra Motor as an agent for motorized vehicles today and how the exemption procedure for imported goods belonging to foreign representatives in Indonesia should be by the Decree of the Minister of Finance Number 90/KMK.04/2002 concerning Procedures for Granting Import Duty and Excise Exemption on Goods of Representatives of Foreign Countries and The official. This research is a normative legal research that uses secondary data as a source. The secondary data sources consist of laws and regulations, books, journals, records, and others, which can be obtained through library research and analyzed using qualitative data analysis methods. This study found the exemption procedures related to import duties and excise by the Directorate General of Customs and Excise according to the current Indonesian legal regulations for goods transactions between the British Embassy in Indonesia and PT. Toyota Astra Motor, a motor vehicle agent legal entity in Indonesia, has a rigid flow that can cause losses to one of the parties in its implementation. On this basis, it is necessary to amend the procedure for the exemption of import duty and excise in Indonesian legal regulations and clarify the meaning of exemption and return to provide benefits to both parties. These advantages include PT. Toyota Astra Motor, as the Seller, gets a refund of the import duties that have been paid previously. In this case, the British Embassy can get the goods from the sale and purchase quickly without waiting for the delivery process.